2002
DOI: 10.1021/jo016000e
|View full text |Cite
|
Sign up to set email alerts
|

Domino Metathesis of 2-Azanorbornenones:  A New Strategy for the Enatioselective Synthesis of 1-Azabicyclic Compounds

Abstract: Domino metathesis of N-alkylated derivatives of (1S)-2-azanorborn-5-en-3-one allowed for the enantioselective synthesis of pyrrolizidine, quinolizidine, pyrrolidinoazepine, and pyrrolidinoazocine derivatives in a straightforward process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…In these runs, desired seven‐membered heterocycles 9b , 9d and 9e were eventually obtained cleanly after a second metathesis reaction, which was performed on the purified bicyclic product in the absence of vinyl acetate (see the Supporting Information). These observations indicated that this metathesis sequence takes place in the order of regioselective ROM, CM and RCM 15. Nitrogen protecting groups were found to have no significant effect on these metathesis reactions (Table 1, run 7 vs. run 8).…”
Section: Resultsmentioning
confidence: 88%
“…In these runs, desired seven‐membered heterocycles 9b , 9d and 9e were eventually obtained cleanly after a second metathesis reaction, which was performed on the purified bicyclic product in the absence of vinyl acetate (see the Supporting Information). These observations indicated that this metathesis sequence takes place in the order of regioselective ROM, CM and RCM 15. Nitrogen protecting groups were found to have no significant effect on these metathesis reactions (Table 1, run 7 vs. run 8).…”
Section: Resultsmentioning
confidence: 88%
“…Ethenolysis of the norbornene substrate 37 catalyzed by first‐generation Ru1 led to the triene 38 in excellent yield without further cyclization, even after prolonged treatment at high temperature (Scheme ) . Treating 38 with second‐generation Ru2 led to complete ring‐closing metathesis to give 39 , showing the drastic influence of the nature of the catalyst in metathesis events . Notably, direct treatment of 37 with Ru2 under ethylene atmosphere led to a poor yield in 39 .…”
Section: Applications In Fine Chemistrymentioning
confidence: 99%
“…Some previous examples in which a pendant olefinic group is in the vicinity of a strained cyclic olefin (Scheme , 40 and 41 ) revealed the possibility of cascade ring‐opening/ring‐closing metathesis in competition with the sole ring opening upon ethenolysis . In principle, such cascades, which lead to skeleton rearrangements, are possible in the absence of ethylene.…”
Section: Applications In Fine Chemistrymentioning
confidence: 99%
“…[51] Treating 38 with second-generation Ru2 led to complete ring-closing metathesis to give 39, showingt he drastic influence of the nature of the catalysti n metathesis events. [51,52] Notably,d irect treatment of 37 with Ru2 under ethylene atmosphere led to apoor yield in 39.…”
Section: Ethenolysis Of Strained and Small Rings:formation Of Dienesmentioning
confidence: 99%